Contrasting Role of Dose Increase in Modulating Sofosbuvir-Induced Hepatocyte Toxicity - Yousefsani, Bahare Sadat; Nabavi, Nasim; Pourahmad, Jalal (Drug Research, 2020)
Sofosbuvir, the oral direct-acting antiviral, is a medication, which used as the effective treatment for hepatitis C infection. Although sofosbuvir thought to have few adverse-effects, there have been some experiences of serious drug-induced hepatotoxicity. In this research, the molecular/cellular pathways that lead to sofosbuvir-induced hepatotoxicity were evaluated on isolated rat hepatocytes. Rat hepatocytes were isolated using collagenase reperfusion technique. In evaluating the different pathways of sofosbuvir-induced hepatotoxicity, ROS formation, mitochondrial membrane potential collapse, lysosomal membrane damage, glutathione depletion, and the percentage of apoptosis versus necrosis were determined. Our data demonstrated that the cytotoxic effect of sofosbuvir in lower concentrations (25, 50 and 100 µM) is mediated by above stream pathways. On the other hand, sofosbuvir acts in opposite directions at higher concentrations (400 µM) and acts as an antioxidant and hepatoprotective. We concluded that sofosbuvir while looking toxic and pro-oxidant in lower concentrations, acts as protective and antioxidant in higher concentrations.
Keywords: sofosbuvir; oxidative stress; hepatotoxicity; mechanism; cytotoxicity; antioxidant